LONGITUDINAL CORRESPONDENCE OF GROWTH IN DIFFERENT INDICATORS OF HEALTH. (16th November 2018) - Jones, J; Geiser, C; Fauth, E
Abstract: Multiple indicators of self-rated health exist and are valuable proxies for health in older adults. Self-rated health is commonly assessed with one question and commonly take one of three common wordings where participants are asked to rate their health in general, compared to a year ago, or compared to others in their cohort. Previous research has compared these forms to one another in terms of predicting outcomes and return conflicting results. Despite the conflicting research indicating the different forms are either analogous or distinct, the extent to which indicators measure similar trajectories over time has not been assessed. The present study used an indicator specific growth curve model with categorical indicators to assess the homogeneity or heterogeneity in growth processes. Assessments were made on the three commonly used forms of self-rated health. Results from the indicator specific growth curve model showed similar trajectories for only two of the indicators. Specifically, general self-rated health and health compared to others showed similar and significant propensities to decline in ratings over time. Conversely, health compared to a year ago showed no propensity to change over time. Despite the differences in propensity to change over time, the correlations between growth factors were high and significant in all cases, indicating a homogeneity in the change process. The results of the present study highlight homogeneity in the growth process and warrant utilization of multiple indicator growth processes in future self-rated health assessments.